Prevalence of and traits associated with low BMD among female adolescent runners - Barrack, M. T.; Rauh, M. J.; Nichols, J. F. (Medicine & Science in Sports & Exercise, 2008)
Purpose: Identify the prevalence of and traits that may increase the risk of low bone mineral density (BMD) among 93 female adolescent competitive endurance runners.